Nonvascular drug-eluting stent coated with sodium caprate-incorporated polyurethane for the efficient penetration of paclitaxel into tumor tissue. (March 2015) - Jeong, Dooyong; Lee, Don Haeng; Lee, Dong Ki; Na, Kun
To increase the therapeutic potency of nonvascular drug-eluting stents, sodium caprate was employed as a drug-penetration enhancer. A polytetrafluoroethylene-covered drug-eluting stent was coated with a mixture containing sodium caprate, paclitaxel, and polyurethane via the rolling coating technique. The coated stent has a smooth membrane surface with a 40-µm membrane thickness. Paclitaxel was released from the coated stent for two months. In the multilayered cell sheet model, sodium caprate in the polyurethane membrane (PUSC10) showed the possibility of enhancing the paclitaxel tissue penetration. The amount of penetrated paclitaxel for the sodium caprate-containing polyurethane membrane (PUSC10) was two times higher than that of sodium caprate-free polyurethane membrane. Additionally, the potential of sodium caprate was confirmed by a tumor-bearing small animal model. PUSC10 incorporated with Nile red (as a model fluorescence dye for visualization of drug penetration; PUSC10–Nile red) or PUSC10 incorporated with paclitaxel (PUSC10–paclitaxel) membrane was implanted at tumor sites in Balb/c mice. In the case of PUSC10–Nile red, the tissue penetration depth of Nile red was significantly increased from 30 µm (without sodium caprate) to 1060 µm (with sodium caprate). After seven days, an almost four times higher therapeutic area of PUSC10–paclitaxel was observed compared to that of polyurethane–paclitaxel (without sodium caprate) by a terminal deoxynucleotidyl transferase dUTP nick end labeling assay. The results indicate that sodium caprate improves the penetration and therapeutic efficiencies of drugs in drug-eluting stents, and thus, it has potential for local stent therapy.